Prevalence of major depression and symptoms of depression in patients with HTLV-1 infection - Souza, Alessandro R.M.; Thuler, Luiz Claudio S.; Lopez, J. Ramón R.A.; Sohler, Marzia Puccioni (Brazilian Journal of Sexually Transmitted Diseases, 2009)
Introduction: major depression occurs at a rate of 2 to 6.6% in the population at large and 5 to 10% in hospitalized patients. Objective: to evaluate the prevalence of the major depression episode and of symptoms of depression in patients infected with the HTLV-1 virus. Methods: we prospectively selected 36 patients infected with the HTLV-1 virus. The diagnosis for depression was based on the DSM-IV (Diagnostic and Statistical Manual of Mental Disorders) criteria. In all of the depressed patients, we applied the Hamilton scale (HAM-D 21 items) in order to quantify the disease. Results: ten participants (28%) had major depression. Seventy-seven percent presented at least one symptom of depression. The most prevalent symptoms consisted of sleep disturbances, changes in appetite and anhedonia. Conclusion: we found a higher prevalence of depression among patients infected with the HTLV-1 virus. The authors emphasize the importance of investigating symptoms of depression in patients infected with HTLV-1